Wars of National Liberation - Moran, Daniel; General Editor : Keegan, John (London Cassel, Wellington House, 2001)
Photographs and text explore the reasons for and the way in which wars have been fought over the last half of the twentieth century.
Include Pictures, Maps and Index
Keywords: Developing Countries -- Politics and Government -- World politics -- 1945-1989 -- National Liberation Movements